Analysis of Teachers as Role Models in Strengthening the Character of Elementary School Students: Phenomenological Study at SDN Tegal Alur 08 Pagi - Jumatullailah, Siti Nurfebri; Nina Nurhasanah; Nidya Chandra Muji Utami (At-Taqaddum, 2025)
This study aims to describe and analyze the profile and process of teachers who act as models in strengthening students’ character, as well as to identify their weaknesses and strengths in performing this role. The research is relevant to current educational issues concerning the importance of character education and the need for teachers to serve as moral exemplars for students. This study employed a qualitative method with a phenomenological approach conducted at SDN Tegal Alur 08 Pagi, involving six teacher participants selected purposively. Data were collected through observation, interviews, and document analysis, and analyzed using NVivo software. Data validity was ensured through confirmability, credibility, transferability, and dependability. The findings indicate that teachers’ profiles as role models in character education are reflected in habituation programs, active learning, and continuous reflective approaches supported by professional competence and integrity. The process of character strengthening is carried out systematically and sustainably through multifaceted roles and techniques applied both inside and outside the classroom. Challenges experienced by teachers include limited facilities, family environmental influences, and emotional pressure in balancing academic and moral responsibilities. Meanwhile, teachers’ strengths lie in their consistency as role models, close relationships with students, the use of persuasive discipline, creative learning approaches, and the holistic integration of character values supported by the school’s vision and mission. From a phenomenological perspective, the study highlights how teachers interpret their experiences as moral models, viewing character education as a reciprocal process of learning and reflection rather than a one-way teaching effort.